PENGARUH MODEL PEMBELAJARAN VALUE CLARIFICATION TECHNIQUE (VCT) TERHADAP HASIL BELAJAR DAN KARAKTER TOLERANSI SISWA KELAS IV SD INPRES BTN IKIP I MAKASSAR - Siti Zalzabila Ibrahim; Abdul Azis; Musdalifah Syahrir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the tolerance attitudes and learning outcomes offourth-grade students at SD Inpres BTN IKIP I, which are partly caused by the useof passive methods. Therefore, this study aims to examine the effect of the ValueClarification Technique (VCT) learning model on learning outcomes and tolerancecharacter.This quantitative study used a one-group pretest-posttest design with asample of 25 fourth-grade students at SD Inpres BTN IKIP I selected throughsampling. Data were collected using learning outcome tests, tolerance characterquestionnaires, and documentation. Data analysis involved descriptive statistics,normality tests, and paired-sample t-tests.The results showed that theimplementation of the VCT model significantly improved students' learningoutcomes and tolerance character. Average learning outcomes increased from55.13 to 85.86, and tolerance character scores increased from 42.6 to 90.2. Thisconsistent and even improvement demonstrates the effectiveness of VCT inhelping students internalize Pancasila values, think critically, and develop positivesocial attitudes